1999
DOI: 10.1076/opep.6.2.105.1561
|View full text |Cite
|
Sign up to set email alerts
|

The role of past intake of vitamin E in early cataract changes

Abstract: Prior vitamin E supplementation may protect VECAT participants from developing at least early cortical cataracts. No apparent protective role in terms of nuclear opacities and nuclear color was found regardless of the level, regularity or duration of intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Upon closer examination, forty-seven articles were excluded for the following reasons: thirty-six articles were irrelevant to the interest of the exposure or the outcome, seven articles (30)(31)(32)(33)(34)(35)(36) did not provide OR/RR and its 95 % CI, three articles (37)(38)(39) were duplicated studies and one article (40) was a review. Finally, twenty-seven articles (6,(10)(11)(12)(13)(15)(16)(17)(19)(20)(21)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) were included in the present meta-analysis. The detailed literature search for article inclusion is shown in Fig.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon closer examination, forty-seven articles were excluded for the following reasons: thirty-six articles were irrelevant to the interest of the exposure or the outcome, seven articles (30)(31)(32)(33)(34)(35)(36) did not provide OR/RR and its 95 % CI, three articles (37)(38)(39) were duplicated studies and one article (40) was a review. Finally, twenty-seven articles (6,(10)(11)(12)(13)(15)(16)(17)(19)(20)(21)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) were included in the present meta-analysis. The detailed literature search for article inclusion is shown in Fig.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…First, the dose of supplementation used differed in the different original studies, and the use of high-dose vitamin E supplements may be associated with increased risk of ARC. Second, in the total of ten included studies on supplemental vitamin E intake and ARC risk, five were randomized controlled trials (19,20,44,47,52) that were based on populations with different nutritional status. In addition, in two randomized controlled trials (19,47) the subjects were volunteers, thus volunteer bias might be introduced.…”
Section: Rrmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Vitamin E and Cataract Prevention Study, Nadalin et al [60] showed that when Australian women and men (55-80 years old) were orally supplied with vitamin E (500 IU/day), there was a significant association between prior vitamin E supplementation and the absence of cortical opacity, after adjusting for age, while there was no apparent protective role of prior vitamin E supplementation in terms of nuclear opacity and nuclear color regardless of the level, regularity or duration of vitamin E intake. Olmedilla et al [61] have shown in elderly Spanish women with age-related cataracts that when improvement of visual function is compared between subjects supplied with and without ␣-tocopherol (100 mg/day) for 24 months, this vitamin E supplementation has no beneficial effect on the visual performance.…”
Section: Effect Of Vitamin E Supplementation On Cataract Development mentioning
confidence: 99%